2021
DOI: 10.3389/fmed.2021.671678
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy for Venous Leg Ulcers: A 6 Year Retrospective Study of Results of a Single Center

Abstract: Background: Venous leg ulcers (VLUs) are common and have a large impact on healthcare budgets worldwide. Hyperbaric oxygen therapy (HBOT) may improve healing of these ulcers.Methods: Retrospective, single-center cohort study between 2013 and 2019. All patients with a VLU from an outpatient clinic providing HBOT and wound care were included. The primary outcome measure was wound healing, determined at discharge from the center. Other outcome measures were improvement in patient related outcome measures (PROMs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
(41 reference statements)
1
7
0
Order By: Relevance
“…Having a lower number of sessions or severe signs of PAOD was associated with worse outcomes in the current study. This finding corroborates earlier research, which indicated that undergoing 30 or more HBOT sessions is associated with a successful outcome in chronic wounds 29,31 . The presence of severe PAOD is an important independent risk factor for lower extremity amputations 32 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Having a lower number of sessions or severe signs of PAOD was associated with worse outcomes in the current study. This finding corroborates earlier research, which indicated that undergoing 30 or more HBOT sessions is associated with a successful outcome in chronic wounds 29,31 . The presence of severe PAOD is an important independent risk factor for lower extremity amputations 32 .…”
Section: Discussionsupporting
confidence: 90%
“…This finding corroborates earlier research, which indicated that undergoing 30 or more HBOT sessions is associated with a successful outcome in chronic wounds. 29,31 The presence of severe PAOD is an important independent risk factor for lower extremity amputations. 32 The present findings therefore seem to reflect clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In United States, the annual expenditure for VLUs care amounts to approximately $15 billion 4 . Recent studies have indicated an increasing incidence of VLUs, adding to the burden faced by healthcare systems 5,6 . These ulcers are notorious for their prolonged healing times, frequent recurrence, and substantial impact on patients' quality of life 4,7 …”
Section: Introductionmentioning
confidence: 99%
“…4 Recent studies have indicated an increasing incidence of VLUs, adding to the burden faced by healthcare systems. 5,6 These ulcers are notorious for their prolonged healing times, frequent recurrence, and substantial impact on patients' quality of life. 4,7 The development of VLUs is intricately linked to the pathophysiology of chronic venous insufficiency, characterized primarily by venous hypertension and small vessel damage.…”
Section: Introductionmentioning
confidence: 99%